Future of Work: Implication of Green Economy on Employment Dynamics in Egypt - Elgohary, Sarah Adel (AUC Knowledge Fountain, 2025)
Is Egypt's green economy a reality or just a policy-level aspiration? This thesis explores the tangible impact of the green economy on Egypt's labor market by examining key sectors—automotive, agriculture, and renewable energy. Through qualitative interviews and focus group discussions with private sector representatives, the study assesses the true implications of the green transition from a business-level perspective, beyond the propaganda and hype surrounding climate policies. What is the current scale of the green economy in Egypt's labor market? What existing policies and regulatory frameworks are in place to support the green economy transition? how urgent is the transition to a green economy across different sectors in Egypt? Are there significant changes in the workforce composition, including the emergence of new occupations or modifications to the tasks of existing roles, because of the green economy transition? The findings reveal that the green economy in Egypt is still in its early stages, with some sectors advancing more quickly than others. Agriculture stands out as the most dynamic sector, with the highest urgency to adopt sustainable practices and create green jobs. Across all sectors, changes in workforce composition are occurring, with new roles emerging, particularly in renewable energy, while other sectors are adapting by evolving existing tasks and skills to meet the demands of the green economy.